Identification method for simplified decoupling control system of multivariable processes - Vo Lam Chuong; Truong Nguyen Luan Vu (Journal of Technical Education Science, 2017)
In this paper, a new method of system identification for a multivariable process is adopted to obtain system models from a pair of priori input/output data. Decoupling techniques are the suitable choice for most industrial processes wherein the interactions between process variables are significant. In this work, simplified decoupling is suggested for a two-input, two-output (TITO) process and then a method of controller design for multi-loop systems is proposed. A new analytical tuning method for a proportional-integral-derivative (PID) controller is also proposed for the second-order plus time delay (SOPTD) process model. The tuning parameters of the controller are calculated and simulated in Matlab. When the resulting PID characteristics confirm that the proposed controllers hold good responses, we implement the controller in real-time using PCI card to substantiate our proposed method in a real application.